Robinow (fetal face) syndrome: report of a boy with dominant type and an infant with recessive type - Kantaputra PN. (2014)
The cases of two patients with Robinow fetal face syndrome, an 11-year-old Thai boy and a newborn Caucasian girl, are described. The Thai boy had the characteristics typical of the dominant type of the syndrome with a few newly recognized signs, including communicating hydrocephalus, underdeveloped sinuses, short roots of the teeth, narrow and thick-floored pulp chambers, hypoplastic nipples, absent middle phalanges of the second to fifth toes, cone-shaped epiphyses of the second and fourth fingers and fifth toes, single creases of the fourth and fifth fingers, clinodactyly of the third fingers, dysmorphic umbilicus, and shawl scrotum. The girl had anomalies typical of the recessive type of the syndrome. She also had capillary hemangioma at the tip of her nose and hypoplastic fourth metatarsal bones, which are the newly recognized features of the recessive type. Infrequently reported clinical manifestations of the syndrome are discussed.